Calcifying fibrous tumor and inflammatory myofibroblastic tumor are epigenetically related: a comparative genome-wide methylation study - Tomassen, Tess; Kölsche, Christian; de Leng, Wendy W. J.; Kommoss, Felix; Voijs, Carmen M. A.; Peeters, Ton; van Noesel, Max M.; Creytens, David; van Gorp, Joost M.; Petersen, Iver; Vokuhl, Christian Oliver; Deimling, Andreas von; et al. (Annals of diagnostic pathology, 2019)
Based on histological findings, calcifying fibrous tumor (CFT) may be a late (burned out) stage of inflammatory myofibroblastic tumor (IMT). This concept, however, has not been proven by molecular means. Five CFTs were analyzed for IMT-related rearrangements in ALK, ROS1 and RET using fluorescence in situ hybridization (FISH). Additionally, genome-wide methylation patterns were investigated and compared with IMT (n=7), leiomyoma (n=7), angioleiomyoma (n=9), myopericytoma (n=7) and reactive soft tissue lesions (n=10) using unsupervised hierarchical cluster analysis and t distributed stochastic neighbor embedding. CFT patients, 4 females and 1 male, had a median age of 20years ranging from 7 to 43years. Two patients were younger than 18years old. The tumors originated in the abdomen (n=4) and axilla (n=1). Histologically, all lesions were (multi) nodular and hypocellular consisting of bland looking (myo)fibroblasts embedded in a collagenous matrix with calcifications. FISH analysis brought up negative results for ALK, RET and ROS1 rearrangements. However, genome-wide methylation analysis revealed overlapping methylation patterns of CFT and IMT forming a distinct homogeneous methylation cluster with exception of one case clustering with myopericytoma/angioleiomyoma. In conclusion, DNA methylation profiling supports the concept that CFT and IMT represent both ends of a spectrum of one entity with CFT being the burn out stage of IMT.